Aplicación de la contabilidad gerencial al sindicato de choferes profesionales del cantón La Maná, provincia de Cotopaxi, año 2009 - Paucar Ojeda, Lucía Elizabeth (2012)
The application ofmanagement accountingallowed to get accounting informationonthe businessactivities which were carried out on time. It permitted to knowthe activities that generatevalueand the ones that do notin order toeliminate ordiminish them according the case; and the economic situation ofthe institution was determined. The research was developedthroughinterviewsand surveys, so the collection of the informationshowedthe lack ofmanagement accounting….